Fostering Awareness of Social Sustainability in Digital Business - Serrano, Julio C.; Diduc, Sniazhana; Šilenskytė, Aušrinė; Stephens, Melodena; Nava-Aguirre, Karla Maria (Palgrave Macmillan, 2024)
With the increasing adoption of advanced technologies for designing innovative business models, business success relies heavily on the competencies needed to intelligently and responsibly utilize various technologies to create value. This chapter introduces teaching activities that equip business graduates with the competencies required to utilize advanced technologies, such as generative artificial intelligence (AI) and blockchain, for digital business in a socially sustainable manner. Awareness of social sustainability is crucial in digital business development and management, as such business makes both positive and negative societal impacts globally and within local communities. For example, adoption of advanced technologies in digital business may result in the need for workforce re-skilling, potential job losses, changes in consumer behavior, and the ability to either obscure or enhance transparency in global value chains. To promote digitalization that is socially sustainable, this chapter offers hands-on exercises grounded in Kolb’s experiential learning framework. These exercises immerse learners in the realities of digital business, increasing the opportunities and threats that technology utilization may bring. The learners get to explore AI and blockchain applications, reflect on their societal implications, and devise solutions that prioritize social sustainability. Thereby, this chapter supports the implementation of specific Sustainable Development Goals (SDGs): SDG 9 (Industry, Innovation, and Infrastructure), SDG 10 (Reduced Inequalities), SDG 12 (Responsible Consumption and Production), and SDG 16 (Peace, Justice, and Strong Institutions).
Keywords: Digital business; Experiential learning; Artificial intelligence (AI); Blockchain; social sustainability; fi=Henkilöstöjohtaminen|en=Human Resource Management|; fi=Strateginen johtaminen|en=Strategic Management|